Does The Price Puzzle Exist in Colombia? Empirical Evidence and Policy Implications - Blen Solomon; Isabel Ruiz (Ecos de Economía, 2006)
The price puzzle has been the focus of many studies, however, most of these studies have focused on developed economies and especially on the U.S. Owing to this tendency; we do not know if there is existence of a price puzzle in developing economies. This is an important topic of research as it facilitates the understanding on the different channels of monetary policy. It also helps our understanding regarding monetary policy effectiveness and in the context of the Colombian economy, this is a main issue as the basic long-term target of Colombia’s monetary policy is price stability. This study investigates the existence of the price puzzle for the period 1980:5-2003:12 in Colombia by using Vector Error Correction Model (VECM). Since the sample period of study is not characterized with a uniform monetary policy regime, following Balke and Emery (1994) we divide our sample period according to existent structural breaks. We test for the price puzzle by dividing our sample into pre-1991 period (before inflation targeting started) and during inflation targeting period. We employ impulse response functions as our main tolos to investigate the price puzzle. The impulse response functions show that during both the pre-1991 and post 1991 periods, prices don’t rise in response to positive shocks in short term interest rates. Therefore we conclude that Colombia does not exhibit the price puzzle. In fact, during both periods as well as the whole sample period, prices are not responsive to short-term interest rate shocks. The unresponsiveness of prices to positive interest rate shocks is not expected since we would anticipate prices to decrease due to a positive interest rate shock